Post-compulsory schooling of youth in Turkey during the Great Recession: A case of pro-cyclical enrollment - Murat Demirci; Meltem Poyraz (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
The impact of recessions on school enrollment is ambiguous. On one hand, recessions might increase the likelihood of enrollment due to decreasing opportunity costs of attending school. On the other hand, recessions might discourage enrollment due to reductions households have in funds available for education and deteriorating expectations about returns to education. In this paper, we empirically analyze how local unemployment rates affect enrollment decisions in Turkey during the period covering the Great Recession of 2008-2009. Our estimates show that the likelihood of enrollment in university undergraduate programs decreases during periods of and in regions experiencing higher unemployment, whereas the enrollment in high schools is not affected. This finding contradicts earlier findings of counter-cyclical enrollment in the context of developed countries. This contrast highlights the variations in the relative importance of the effect of income and expectations and in the potential long-term effects of recessions across countries. In particular, recessions might have longer-lasting negative effects in developing countries due to their adverse effect on human capital accumulation.
Keywords: E24; E32; I20; J24; 330; The Great Recession; School enrollment; Human capital accumulation; Unemployment; Turkey